Manejo contable de los pasivos de la Empresa Ferticosta S. A. de la ciudad de Guayaquil, periodo 2021-2022. - Gamarra Arciniega, Melany Nallely (2023)
For every company, accounting management is an essential procedure to keep efficient control of all economic activities in order to avoid irregularities that may put the organization at risk. Inadequate accounting management not only affects the registration process, but also allows the existence of errors or omissions in the accounting entries; For this reason, an efficient treatment of financial and accounting information is essential. The objective of this study is to determine the accounting management of liabilities in the company Ferticosta S A in the city of Guayaquil in the periods 2021-2022 through the review of the company's accounting information. The methodology used consisted of a mixed study, the types of research used were bibliographic and documentary; while the methods used are inductive and deductive. The investigative techniques considered were an interview and observation of the accounting records of the company. The results determined that the accounting management of the liabilities in the Ferticosta S.A. Company is not efficient due to the fact that errors and omissions were evidenced in the accounting records of the liabilities and one of the main weaknesses of the company with respect to the accounting management of the liabilities is that it does not have accounting policies that guide the procedures in accounting management.